INFLUENCE OF SUNFLOWER (HELIANTHUS ANNUUS) SOWING DATES ON ITS PRODUCTIVITY IN THE WESTERN FOREST-STEPPE - Lykhochvor В.; Kvitko А.; Vynnytskyi В. (Bulletin of Lviv National Environmental University. Series Agronomy, 2024)
The research aimed to investigate how sowing dates and methods affect the yield of the Sumiko hybrid sunflower in the Western Forest-Steppe of Ukraine. The field research took place from 2022 to 2023 at the experimental field of the Department of Technologies in Crop Production of Lviv National Environmental University. The soil in the research area is dark gray, podzol light loam with a humus content of 2.4%. In the first year of the research, the climatic conditions were specific. In 2023, April to May was relatively cold, especially the first half of April, which had low temperatures (less than 10 °C). Additionally, dry weather set in. April saw sufficient precipitation (61 mm), but the rains only lasted until April 17. May received very little rain, with only 13 mm at the end of the month. These conditions were not favorable for sunflower growth, especially for the May sowing period, and they affected productivity levels. In 2024, the growth conditions were more favorable. The timing of sowing significantly influenced sunflower productivity. The highest yield, averaging 3.82 t/ha, was achieved when sowing was done on April 30 using three different methods. Sowing on April 20 also resulted in a high yield of 3.73 t/ha. However, early sowing on April 10 led to a notable decrease in productivity by 0.30 t/ha due to the insufficient April heat. Sowing on May 10 resulted in a yield of 3.48 t/ha, 0.34 t/ha less than the April 30 sowing. Sowing on May 20 resulted in even lower productivity of 3.04 t/ha, a 0.78 t/ha (20.4%) decrease compared to the most productive sowing date. The impact of sowing methods on sunflower yield varied based on the sowing period. The row method (15 cm) demonstrated an advantage across all sowing periods. However, for sowing on April 10, May 10, and 20, the difference between sowing methods was insignificant. Notably, for the highest-yielding periods, the method of sowing significantly influenced yield formation. For instance, when sowing on April 20 in wide rows (70 cm), the yield was 3.53 t/ha, while narrowing the rows to 45 cm increased the yield to 3.78 t/ha, a difference of 0.25 t/ha. The highest yield of 3.88 t/ha was achieved with the row sowing method, surpassing the 70 cm rows by 0.35 t/ha (9.9%).